Intergenerational conflict, partisan politics, and public higher education spending: evidence from the German states - Ulrich Oberndorfer; Viktor Steiner (Institute for the Study of Labor (IZA), 2006)
We analyze potential effects of demographic change and political constellations on higher education spending. In our panel analysis of west German states (Laender) for the period 1985 to 2002 we find empirical evidence for the hypothesis of a negative relationship between demographic aging and spending on public higher education. In contrast to the hypothesis of the classical partisan theory that implies higher public expenditures under leftist parties, we find that governments under conservative parties or a coalition between social democrats and conservatives spend more on public higher education than governments run by the social-democratic party alone.
urn:nbn:de:101:1-20090309111
Keywords: 330